Pengembangan Aplikasi Perhitungan Nilai Understandability Berdasarkan Rancangan Perangkat Lunak - Mochammad Adhy; Bayu Priyambadha; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Understandability is a software quality parameters that shows the level of ease in understanding a developed software module. As an example of the importance of understandability, in an experiment on code inspection, 60% of issues reported by professional reviewers on maintenance are related to understandability. Therefore this research is intended to develop an application that can measure the level of understandability automatically in the software design phase. Measurement of understandability is done in by using multivariate understandability metric. The development is done by adopting the waterfall model methodology. Based on the results, 100% of requirements are validated. As for the system efficiency, system was able to complete 1 measurement task within 10 seconds, and the user can complete 100% of the task, which proved that system is capable to measure understandability efficiently. As for the relationship between understandability results shows by the system and maintainability that has been known shows the spearman's rank correlation of 0.987, which pointing the results of system can be used as one of the reference to estimating the effort to performing maintenance in early stage of software development.